Nilai-Nilai Pendidikan Kesetiaan Devī Sāvitrī Dalam Vāna Parva - Kadek Hemamalini (Jurnal PASUPATI, 2018)
This study discusses about the value of teaching the loyalty of Devi Savitri in Vana Parwa. This theme was created based on the phenomenon of the declining value of faithfulness between husband and wife in married life, as they appear in the mass media and real life which are affairs and divorce in marriage. Related to that phenomenon, writer invites people began to improve itself by studying Hindu literature. Which one of them is Devi Savitri's story in the Vana Parva, which can be used as guidance in run a married life. This study tried to explore the value of teaching the loyalty of Devi Savitri in Vana Parwa, as well as its still  relevance in this era. This research is a literature study. Using the concept the value of teaching the loyalty of Devi Savitri, and Vana Parva. The results of this study found that  Devi Savitri was the wife who uphold the Satya concepts, such as Satya Wacana, Satya Hredaya, Satya Laksana, Satya Mitra and Satya Samaya. Furthermore, Devi Savitri also act with love and devotion to her family.  In order to the values and the concepts can be applied  in this era.